Analysis of The Effectiveness of Fraud Prevention Through The Implementation of Guidelines for Handling Conflicts of Interest in The Ministry of Finance - Galih Teguh Gumilang (Interdisciplinary Social Studies, 2025)
This study aims to analyze the effectiveness of fraud prevention through the implementation of the Decree of the Minister of Finance (KMK) Number 475 of 2023 concerning Guidelines for Handling Conflicts of Interest within the Ministry of Finance of the Republic of Indonesia. The qualitative research method was used by in-depth interview techniques with two regulators and three policy users, as well as secondary data analysis such as complaint reports and implementation statistics. The results of the study show that KMK 475/2023 has succeeded in increasing employee awareness of integrity through the employee data declaration mechanism (DDP) and technology-based supervision. However, key challenges include a lack of leadership commitment, low participation in internal reporting, and the need for increased transparency and speed of complaint follow-up. These guidelines have proven to be effective in reducing fraud risk, especially through preventive and early detection approaches, although optimizing socialization, whistleblower protection, and technology integration is still needed to achieve maximum results. This research is expected to contribute to increasing the effectiveness of fraud prevention within the Ministry of Finance.